A Modified Graphical Method to Target the Regeneration Stream Flow Rate for Water-Using Networks - J.-F. Zhu; D.-L. Xu; Z.-L. Liu (Chemical Engineering Transactions, 2015)
A few graphical methods in literature, sometimes, cannot give correct Regeneration Pinch and/or target of regeneration stream flow rate for water-using networks. By analysis, this paper points out that the reason for the above problem is that the streams of the processes, which reuse the outlet stream of the processes satisfied by freshwater only, are illustrated incorrectly. Based on the above analysis, a modified method is proposed. The procedure proposed in this article is as follows: (1) draw the Concentration-Cumulative Mass Load Curves (CCMLCs) for the processes which use freshwater only and that for other processes, respectively; (2) identify and remove the processes with high inlet concentrations and can reuse the outlet streams of the processes which are satisfied with freshwater only; (3) from the CCMLCs of the remaining processes with high-inlet concentrations, the target of regeneration stream flow rate and Regeneration Pinch can be obtained. This paper solves the problem of inconsistent results of some graphical methods and that of numerical methods in literature.